The responsibility of port terminals for cargo damage during storage and stowage - Menin Junior, Romeu Felix (Revista Coleta Científica, 2017)
The theme of this article is: The responsibility of port terminals for cargo damage during storage and stowage. The following problem was investigated: Is there an international model being applied in Brazil, a unification of the responsibility of the shipping company for damage to cargo or for losses and delays? The following hypothesis was considered: There is an international understanding of responsibility within port terminals during storage and stowage, as the analysis is done by controllers to operators. The general objective is: To analyze the exclusion clauses of responsibility of the operator during the storage and stowage operations. The specific objectives are: The shipowner's responsibility; Damage to cargo, losses and delays. This work is important for the operator of the Law and for society as a whole, as it addresses the reflexes resulting from an institute that is little talked about academically today and is legally relevant. As a result of the research carried out, it is concluded that: In the maritime transport of goods, contractual civil liability for damages, losses and delays resulting from the non-fulfillment of contractual obligations, attached to the transport contract or charter contract, is inserted. This is a qualitative theoretical research lasting six months.